2020
DOI: 10.3390/ani10030442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microencapsulated Blends of Organics Acids (OA) and Essential Oils (EO) as a Feed Additive for Broiler Chicken. A Focus on Growth Performance, Gut Morphology and Microbiology

Abstract: The goal of the trial was testing the effects of a blend of organic acids and essential oils dietary supplementation on growth performance and gut healthiness in broiler chickens. In total, 420 male Ross 308 chicks (1-day old) were randomly assigned to two dietary treatments: basal (BD) and organic acids and essential oils (OA&EO) diets (three replicates/treatment; 70 broilers/replicate). BD group received commercial diets whereas OA&EO group basal diets + 5 g/kg of microencapsulated organic acids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
3
21
0
2
Order By: Relevance
“…This notable finding was ascertained by the pronounced improvement in the body weight gain and feed conversion ratio as well as decreases in the severity of clinical findings and mortality percentages, especially in the challenged group treated with 2.25% thymol nanoemulsion. In accordance with our study, a reduced mortality rate and an improved growth gain and feed conversion ratio were observed upon supplementation of chicken diet with microencapsulated blends of natural identical essential oils especially thymol [42]. Our present in vivo observations parallel the previous study, which confirmed the antivirulence activities of thymol oil and thymol nanoemulsion against different Salmonella species [43].…”
Section: Discussionsupporting
confidence: 92%
“…This notable finding was ascertained by the pronounced improvement in the body weight gain and feed conversion ratio as well as decreases in the severity of clinical findings and mortality percentages, especially in the challenged group treated with 2.25% thymol nanoemulsion. In accordance with our study, a reduced mortality rate and an improved growth gain and feed conversion ratio were observed upon supplementation of chicken diet with microencapsulated blends of natural identical essential oils especially thymol [42]. Our present in vivo observations parallel the previous study, which confirmed the antivirulence activities of thymol oil and thymol nanoemulsion against different Salmonella species [43].…”
Section: Discussionsupporting
confidence: 92%
“…The present study was designed to evaluate the effects of dietary supplementation of a blend of OA (sorbic and citric acids) and EO (thymol and vanillin), already recognized as improving growth performance [28], in order to highlight the potential effects on quality of meat during refrigerated storage. In our previous trial, we observed certain positive effects on mortality rate, growth performance, gut morphology, inflammation of gut epithelium, with a reduction in Clostridium perfringens load in ileal content and a decrease in mesophilic bacteria and enterococci loads in litter, occurring in the last growing phase [30]. However, this positive finding did not lead to improvements in slaughter performances, which appeared comparable between treatments in terms of carcass yield and cut percentage, even if a higher yield percentage was numerically detected in AVI than in CON carcasses.…”
Section: Discussionmentioning
confidence: 85%
“…Its use, mainly as replacer of antibiotic growth promoters, is well documented either in swine [28] and in poultry, for which it is reported to improve feed intake, food conversion ratio, and to decrease mortality [29]. In a recent study, we observed a reduction in the overall mortality rate and a positive effect on growth rate in the last period of the growing cycle when broiler chicken diet was supplemented with 0.5% of microencapsulated blend of OA and EO [30]. Moreover, in the same study, a favourable effect on gut morphology was also found in different intestinal segments, in the last growing phases.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations